Penelusuran in Silico Potensi Antimalaria dari Karang Lunak Lobophytum sp. sebagai Inhibitor Dihydroorotate Dehydrogenase dari Plasmodium falciparum - Arfan, Arfan; Rayani, Nur; Ode Aman, La (JURNAL FARMASI GALENIKA, 2024)
Malaria is one of the infectious diseases caused by the Plasmodium parasite and remains a persistent health challenge. Therefore, exploring compounds with potential as antimalarials remains a crucial aspect. This study aims to evaluate the identified compounds from the soft coral Lobophytum sp. as antimalarial candidates using molecular docking techniques, predicting their profiles including pharmacokinetic and drug likeness. The identified compounds from this soft coral were successfully docked into the active site of the Plasmodium falciparum's enzyme dihydroorotate dehydrogenase (DHODH) using AutoDock Vina, and pharmacokinetic profiles and drug likeness were predicted using SwissADME. Compounds Saurufuran B and Oxyphyllacinol from Lobophytum sp. exhibited binding affinity energies of -9.4 kcal/mol and -8.6 kcal/mol against DHODH, which were more negative than other compounds but less negative than the inhibitor F1T (-10.7 kcal/mol). These compounds showed hydrogen bonding with amino acids His185, Lys429, Asn458, and Ser505 and hydrophobic interactions with amino acids Cys175, Leu176, Phe188, Ile263, Arg265 of the DHODH enzyme. The pharmacokinetic profile of these compounds revealed good solubility and high gastrointestinal absorption, making them suitable for drug development. These compounds are expected to inhibit the function of CYP450 isoforms as important metabolizing enzymes in the body. Furthermore, Saurufuran B and Oxyphyllacinol also exhibit a safe toxicity profile and meet the drug-likeness criteria based on Lipinski's Rule of Five. These findings suggest the potential of Saurufuran B and Oxyphyllacinol from Lobophytum sp. as DHODH enzyme inhibitors for P. falciparum with favorable affinity predictions and pharmacokinetic profiles for antimalarial drug development.